Will the Growth of the BRICs Cause a Shift in the Global Balance of Economic Power in the 21st Century?. Issue 4 (1st October 2016) - Siddiqui, Kalim
Abstract: Some 42% of the world's population (i.e., 3 billion people) live in Brazil, Russia, India, and China, collectively known as BRICs. Of these four, India and Brazil also have a higher than average birth rate. The combined economy of the BRICs made up 25.6% of the global GDP in 2015 and has been projected to increase to 33% by 2020. Studying the BRICs economies is important for a number of reasons, including their rapid economic growth rates, large populations, and fast-growing markets for goods and capital. Their average per capita annual income ranges from about US$3, 000 to nearly US$15, 000 in PPP terms. However, in 2015 their average annual GDP growth exceeded 6%, which is much higher than the 1.9% of the OECD countries. It is estimated that their share in the world economy could double over the next two decades, from 25.6% to 40%.